Global COVID-19 and Environmental Sciences Research: A Scientometric Analysis of Highly-Cited Publications - Sab M, Chaman; Praveen, A.M; Eshwara, Y; Jali, Shambulinga B; Mueen Ahmed, KK; Yunus, Mohammed (Journal of Data Science, Informetrics, and Citation Studies, 2026)
The COVID-19 pandemic increased exponentially across the global, it has threatened the human lives and uprooted the economy of various countries, besides having a major impact on the environment. The global disruption caused by the COVID-19 has brought about several effects on the environment and climate. Hence a scientometric study of the highly cited global publications in impact on COVID-19 and Environment has been conducted to identify the emerging research trends in this field. The data downloaded Global publications on this topic from the Web of Science database using a well-defined research strategy, which was based on using “keyword” and “Title’ search tags of Web of Science database. The search was subsequently restricted to “Covid-19” and “Environmental Science” subject and limited to 29 years in “global” yielded 2,903 records. The 2,903 publications were published on ‘Covid-19 and Environmental Science’ as searched in web of science database and these have received 126 papers have 1,444 citations from 1≤100 citations, average citation per paper 254.6 from the data spans 1992-2023, covering 126 publications published across 85 different sources, including journals, books, and proceedings. Despite an annual growth rate of 0%, indicating stable but non-expanding research output, the dataset has an impressive average citation per document age is 15.6 years, suggesting that many highly cited papers were published years ago and continue the depth of engagement with existing literature. Regarding document contents, there are 697 keywords plus and 431 authors keywords, demonstrating diverse research themes and indexing strategies. Authorship analysis reveals contributions form 602 authors, with 27 single-authored documents, indicating that most research in this field is collaborative. The average number of co-authors per document is 4.98, with an international co-authorship rate of 29.375, reflecting strong global collaborations. The results of the present study are focused on the evaluation of the Global contribution, focusing on global issues using quantitative and qualitative methods. Such a study has allowed us to visualize the research trends that emerged during the COVID-19 pandemic and will facilitate the researchers to identify significant hotspots and the latest trends in the field.
Keywords: COVID-19; Environmental Science; Global publications; Highly Cited Papers; Scientometrics